What, where and when: spatial foraging decisions in primates. (13th September 2018) - Trapanese, Cinzia; Meunier, Hélène; Masi, Shelly
ABSTRACT: When exploiting the environment, animals have to discriminate, track, and integrate salient spatial cues to navigate and identify goal sites. Actually, they have to know what can be found (e.g. what fruit), where (e.g. on which tree) and when (in what season or moment of the year). This is very relevant for primate species as they often live in seasonal and relatively unpredictable environments such as tropical forests. Here, we review and compare different approaches used to investigate primate spatial foraging strategies: from direct observations of wild primates to predictions from statistical simulations, including experimental approaches on both captive and wild primates, and experiments in captivity using virtual reality technology. Within this framework, most of these studies converge to show that many primate species can ( i ) remember the location of most of food resources well, and ( ii ) often seem to have a goal‐oriented path towards spatially permanent resources. Overall, primates likely use mental maps to plan different foraging strategies to enhance their fitness. The majority of studies suggest that they may organise spatial information on food resources into topological maps: they use landmarks to navigate and encode local spatial information with regard to direction and distance. Even though these studies were able to show that primates can remember food quality ( what ) and its location ( where ), still very little is known on how they incorporate the temporal knowledge of available food ( when ). Future studies should attempt to increase our understanding of the potential of primates to learn temporal patterns and how both socio‐ecological differences among species and their cognitive abilities influence such behavioural strategies.